Evaluation of Quality Control Methods for Foot-And-Mouth Disease Vaccines by High-Performance Liquid Chromatography - Mun-Hyeon Kim; Seon-Jong Yun; Yeon-Hee Kim; Hyang-Sim Lee; Ji-Yeon Kim; Ji-Ye Kim; JeongWoo Kang; Yong-Sang Kim; Min-Goo Seo (Pathogens, 2020)
Foot-and-mouth disease (FMD) is considered one of the highly contagious viral infections affecting livestock. In Korea, an FMD vaccination policy has been implemented nationwide since 2010 for the prevention and control of FMD. Since the vaccines are imported from various countries, standardized quality control measures are critical. In this study, we aimed to validate a high-performance liquid chromatography (HPLC) device in the Animal and Plant Quarantine Agency lab and identify an appropriate FMD vaccine pretreatment method for HPLC—a simple, reliable, and practical method to measure antigen content. Based on the analyses of specificity, linearity, accuracy, repeatability, intermediate precision, limits of detection, and limits of quantification using FMD standard samples, we validated the method using a standard material. Overall, we confirmed that the HPLC technique is effective for the quantitative assessment of the FMD virus 146S antigen in Korea. Using commercial FMD vaccines, we evaluated three separation methods and identified the method using n-pentanol and trichloroethylene as optimal for HPLC analysis. Our HPLC method was effective for the analytical detection of the antigen content in FMD vaccine, and it may be useful as a reference method for national lot-release testing.